MODEL PENINGKATAN KESUKSESAN KARIR OBYEKTIF DAN SUBYEKTIF PADA DOSEN PTIS (PERGURUAN TINGGI ISLAM SWASTA) - Agus Abdullah (Jurnal Ekonomi dan Bisnis, 2017)
The purpose of this research is to improve the objective and subjective career successlecturer at PTIS (private Islamic universities) by stimulating the emotional intelligence, intrinsicmotivation and competence. The population in this study consisted of three Islamic universities inSemarang, namely: Sultan Agung Islamic University (UNISSULA), University of Wahid Hasyim(UNWAHAS) and the University of Muhammadiyah Semarang (UNIMUS). Total questionnairesdistributed to as many as 69 respondents supported by SPSS version 20 as data processorand tools of statistical processing. This study analyzed by linear regression and regressionmoderation. The variables used are: independent variables such as emotional intelligence andintrinsic motivation, moderation variable such as competence and the dependent variable inthe form of objective and subjective career success. The results showed that there is a positiveand significant effect of emotional intelligence on objective and subjective career success andcompetence able to moderate the relationship between intrinsic motivation and career successsubjective.Keywords: Emotional Intelligence, Intrinsic Motivation, Objective Career Success, SubjectiveCareer Success.